Effect of ZrO2 addition on the BO6 vibration modes of [(Bi0.5Na0.5)TiO3 – SrTiO3 – BaTiO3] perovskite structure for enhancement energy storage properties - Mohammed Ezzeldien; Abeer M. Beagan; P.A. Alvi; Abd El-razek Mahmoud (Results in Physics, 2024)
In the present study, (Bi0.35Na0.35Sr0.2Ba0.1) (Ti1-xZrx) O3 (abbreviate BBSNTZx) (0.0 ≤ x ≤ 0.1) bulk ceramics were selected to enhance their energy storage performance and relaxor degree by suppression of TiO6 (Orthorhombic-phase) vibration mode. As a result, a significant effect of Zr4+ on the dilution of O-phase and growth of R-phase has been observed. The addition of Zr4+ induced decreasing the tolerance factor value (τ) from 0.994 to 0.988, which agrees with FT-IR results. Along with the variation of crystal structure, the broad permittivity peak increased via the amount of Zr4+ increases, which was confirmed by increasing the diffusive coefficient (γ) from 1.524 to 1.877. Pure BBSNT anti-ferroelectric –ceramic exhibited high Wrec = 0.57 J/cm3 with moderate ƞ = 83 % at lower electric field (E = 60 kV/cm). The value of ƞ can be enhanced up to 93 % at Zr = 0.1, attributed to enhanced relaxor phase and polar nanoregions contributions.Furthermore, the temperature and frequency stability of the energy storage properties can be enhanced simultaneously by the addition of Zr ions. The suppression of converse piezoelectric coefficient (d*33) attributed to decreasing the non-revisable 180° domain switching at high Zr content. The present study introduces useful guidelines for understanding the correlation between BO6 octahedral tilting vibration mode and ferroelectric properties of the perovskite structure. Furthermore, the energy storage properties can be enhanced by the suppression of TiO6 vibration modes, which is confirmed by decreasing the O/R volume fraction, subsequently enhancing the relaxor degree.